TUDDA NYUMA - LET’S LOOK BACK: A letter to Ham Mukasa - stultiens, andrea; Rumanzi, Canon Griffin (Design/Arts/Culture, 2024)
This contribution is positioned between what might be considered an artistic portfolio and a paper. It is perhaps best understood as a visual essay, in which a speculative correspondence with a prominent Ugandan chief and intellectual, the late Ham Mukasa (ca. 1870-1956), affords the activation of an ambiguous colonial legacy. It aims to complicate and question our relationship to- and understanding of archival materials and the web of privilege and precarity in which they were compiled and exist.